Leg Tremor, An Anxious Patient, A Challenging Treatment - Hana Maizuliana Solehan; M Firdaus A Bakar; Nur Ezzaty Mohammad Kazmin; Wei Ming Tan; Fatimah Zanirah; Sarah Zulaikha Samad; Nor Safiqah Sharil (USIM Press, 2024)
Vol. 8 (2022): Special Issue on Communicable and Non-Communicable Disease, Multidisciplinary Case Reports